The diary of a CEO : the 33 laws of business and life - Bartlett, Steven , 1992- (Flight Books/Penguin Random House UK, 2023)
This is not a book about business strategy. Strategy changes like the seasons. This is a book about something much more permanent. At the very heart of all the success and failure I've been exposed to, both my own entrepreneurial journey and through the thousands of interviews I've conducted on my podcast, are a set of principles that can stand the test of time, apply to any industry, and be used by anyone who is search of building something great or becoming someone great. These are the fundamental laws that will ensure excellence. They are rooted in psychology and behavioral science, are based on the wisdom of tens of thousands of people I've surveyed across every continent and age group, and of course, drawn from the conversations I've had on my chart-topping podcast with the world's most successful people. These laws will work now or in 100 years from now. Are you ready to get started?